Interaksi Sosial Pengembangan Bahasa Anak Tunagrahita Ringan Lev Vygotsky Di SLB Ma’arif Bantul - Laila Almaunah; Wafiyatus Shofy; Noor Chalimah; Kun Faridah; Ahmad Faiz; Yunita Anggraeni; Anisah Uswatun; Bagus Mahardika (PT. Nawa Edukasi Nusantara, 2025)
Children with mild intellectual disabilities have intellectual limitations that affect their cognitive, social, and language development, but they still have potential that can be developed through an appropriate educational process. Developing language skills is an important aspect because language serves as a tool for communication as well as a means for thinking and social interaction. This study aims to analyze the implementation of social interaction in developing the language abilities of children with mild intellectual disabilities at SLB Ma’arif Bantul based on Lev Vygotsky's sociocultural theory perspective. This study uses a qualitative approach with a case study method. Data collection techniques include observation, interviews with teachers, and documentation of learning activities. Data analysis is conducted thematically with reference to the concept of the Zone of Proximal Development (ZPD) and scaffolding. The results of the study indicate that social interaction between teachers, students, and the school environment plays an important role in enhancing the language abilities of children with mild intellectual disabilities, particularly in vocabulary mastery, reading skills, and functional speaking. The teacher acts as a mediator by providing guidance, examples, and repetition according to the child's abilities. However, in its implementation, there are challenges such as differences in students' abilities, difficulty understanding abstract material, unstable emotions in children, and social jealousy. Overall, the application of social interaction based on Vygotsky's sociocultural theory has been proven effective in developing the language skills of children with mild intellectual disabilities, although it still requires adaptive and sustainable learning strategies.